If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 22 = 30 Reorder the terms: 22 + 4x = 30 Solving 22 + 4x = 30 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-22' to each side of the equation. 22 + -22 + 4x = 30 + -22 Combine like terms: 22 + -22 = 0 0 + 4x = 30 + -22 4x = 30 + -22 Combine like terms: 30 + -22 = 8 4x = 8 Divide each side by '4'. x = 2 Simplifying x = 2
| x^2(3+2x)-3(6x+9)=0 | | 6g+3=-(2g+9) | | 0=-42-35r-7r^2 | | 4x+7x+5x=96 | | (2x+1)(2x+1)-9=40 | | 25-(4g+5)=-11 | | y=3y-3 | | (4xy-3xy)= | | -4+3x-6=-16 | | 7*(2x-5)=3*(2-5x) | | -5+3x-6=-16 | | 19x-4= | | 15k^2=25-10k | | 3+2x+6=-53 | | 5x-11= | | 3-x=-1 | | -(-2+4x)-(3-4x)+5=-(-3+6x)+x+1 | | -29+56= | | -4x-1+5x=-13 | | j/20=3 | | 3(x+8)=3x+24 | | x/4+2=-2 | | 22=6+2x | | k+4/2=k+9/2 | | (5x+4)(x-1)=2 | | k+4/2=k+9/4 | | -7x+2+4x=2 | | 40=12x+4 | | 2x-x+3+3x=x+13 | | -7x+2+5x=2 | | 6x^2+5x=-1 | | (2x-5)/3=(2-5x)/7 |